1984
DOI: 10.1007/bf00153791
|View full text |Cite
|
Sign up to set email alerts
|

Polarization of fundamental type III radio bursts

Abstract: The fundamental of type III bursts is only partially polarized, yet all theory for emission near the plasma frequency predicts pure o-mode emission. I argue depolarization is inherent in the burst itself. The o-mode radiation is intensely scattered and mode-converted when it temporarily falls behind its own source and finds itself in the medium that is already disturbed by the electron beam. In particular, mode conversion is very efficient and yet causes only modest angular scattering at the height were ~o _~ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

1985
1985
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…Effects such as mode coupling due to magnetic fields (e.g. Zheleznyakov & Zlotnik, 1964), and scattering due to low-frequency waves (Wentzel, 1984;Melrose, 1989a), or kinetic Alfven waves (Sirenko et al, 2002) during propagation are certainly able to reduce the degree of polarisation but cannot explain why fully polarised emission is never seen. Wentzel (1984) therefore proposed that the emission was depolarised to some extent within the source region itself, and that this was inherent to the emission process.…”
Section: Polarisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Effects such as mode coupling due to magnetic fields (e.g. Zheleznyakov & Zlotnik, 1964), and scattering due to low-frequency waves (Wentzel, 1984;Melrose, 1989a), or kinetic Alfven waves (Sirenko et al, 2002) during propagation are certainly able to reduce the degree of polarisation but cannot explain why fully polarised emission is never seen. Wentzel (1984) therefore proposed that the emission was depolarised to some extent within the source region itself, and that this was inherent to the emission process.…”
Section: Polarisationmentioning
confidence: 99%
“…Zheleznyakov & Zlotnik, 1964), and scattering due to low-frequency waves (Wentzel, 1984;Melrose, 1989a), or kinetic Alfven waves (Sirenko et al, 2002) during propagation are certainly able to reduce the degree of polarisation but cannot explain why fully polarised emission is never seen. Wentzel (1984) therefore proposed that the emission was depolarised to some extent within the source region itself, and that this was inherent to the emission process. For harmonic emission, it was initially thought that the Langmuir waves involved would coalesce head on, and therefore Melrose & Sy (1972); Melrose et al (1978) and the correction by Melrose et al (1980) concluded that harmonic emission must be weakly O-mode polarised.…”
Section: Polarisationmentioning
confidence: 99%
“…Since lower intrinsic polarization can occur only if the initial frequency exceeds the x-mode cutoff frequency (f x cut ), the previous expectation that LMC and nonlinear processes would produce only o-mode radiation meant that depolarization theories were mainly investigated. These include mode coupling [29], scattering by low frequency waves [30,31], and reflection at density inhomogeneities [32]. However, Mjølhus [20] showed that an incident xmode wave perpendicular to B 0 can undergo LMC into an ES wave and a reflected x-mode wave at ionospheric density irregularities.…”
Section: Introductionmentioning
confidence: 99%
“…Wang & Li (1991) have shown that the nonlinear coupling of radio waves with whistlers or ion sound waves explains the nature of the millisecond oscillations in the decimetric radio spike bursts. The conversion of radio emission as o-mode waves into x-mode waves via scattering on ion-sound and whistler waves has been considered by Wentzel (1984) and by Melrose (1988). This mechanism has been used for explaining the weak polarization of radio-bursts of type II and III at metric wavelengths.…”
Section: Introductionmentioning
confidence: 99%